SARS-CoV-2 detection via metagenomic next-generation sequencing of bronchoalveolar lavage fluid/sputum in lymphoma patients receiving B-cell-depleting therapy: a case report of two cases - Sun, Cuiming; Zhang, Zhidan (Frontiers in Medicine, 2025)
We describe two cases of coronavirus disease 2019 (COVID-19) infection in patients with lymphoma receiving B-cell-depleting therapy. Metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF)/sputum showed ongoing viral replication, despite repeated nasopharyngeal swabs being negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA. The patients failed to develop seroconversion of IgG antibodies for SARS-CoV-2. However, they showed favorable clinical outcomes after treatment with nirmatrelvir/ritonavir or molnupiravir, despite the antiviral therapies being initiated later in the clinical course. Our case highlights that in immunocompromised hosts, viral clearance of SARS-CoV-2 in lung tissue may lag behind that in the upper respiratory tract. Thus, alternative diagnostic criteria are necessary, and clinical decisions and interventions should be tailored to each individual case.